Analisis Keputusan Pembelian Susu Sapi Perah Pak Dul - Datul Amaliya, Iva; Purwandhini, Ari Septianingtyas (KUBIS, 2024)
Jember Regency has an area with potential dairy cattle production centers, namely in Kemuning Lor Village, Arjasa District. Therefore, dairy farming needs to be studied in depth. The aim of this research is to determine the factors that influence consumers' purchasing decisions for "Pak Dul" fresh dairy milk and determine the relationship between these factors. The analytical method used is multiple linear regression and PPM correlation test. The results show the factors that influence consumer purchasing decisions for fresh "Pak Dul" dairy milk, namely product quality, price and service quality, which based on the results of the t test analysis shows that there is a significant influence partially or individually from the quality variable products, prices and service quality. Based on the results of the PPM correlation test analysis, the factors between the product quality and price variables have a significant relationship or correlation, while the product quality and service quality variables also have a significant relationship or correlation, compared to the results of the price and service quality variables which do not have a relationship. or not significantly correlated.